INCREASING STUDENTS’ READING COMPREHENSION SKILL BY USING WRITTEN TEXT BOOK - Al Aziz, Edwin Nuvianto; Yusanti, Gita (English Education:Journal of English Teaching and Research, 2020)
Abstract: The purpose of this article is deeply to investigate of some issues about increasing students’ reading comprehension skill by using written text. According to article that I use to support my article states that one of important point in increasing students’ reading comprehension skill is by giving them written text which can attract their interest, such as: comic, novel, short story, storytelling, etc. Some other issues about students’ reading skill are also interesting to be discussed, for example teaching reading methods, the benefits, and the problems which about students’ are reading skill by using written text. The high percentage of success in increasing students’ reading skill is really important to make sure that they have input in mastering or improving their English. However, increasing students’ reading comprehension skill is not easy and it needs to be discussed to figure the best way out.